Isolation and metagenomic identification of Avian leukosis virus associated with mortality in broiler chicken - Bande, Faruku; Arshad, Siti Suri; Omar, Abdul Rahman (Hindawi Publishing Corporation, 2016)
Avian leukosis virus (ALV) belongs to the family Retroviridae and causes considerable economic losses to the poultry industry. Following an outbreak associated with high mortality in a broiler flock in northern part of Malaysia, kidney tissues from affected chickens were submitted for virus isolation and identification in chicken embryonated egg and MDCK cells. Evidence of virus growth was indicated by haemorrhage and embryo mortality in egg culture. While viral growth in cell culture was evidenced by the development of cytopathic effects. The isolated virus was purified by sucrose gradient and identified using negative staining transmission electron microscopy. Further confirmation was achieved through next-generation sequencing and nucleotide sequence homology search. Analysis of the viral sequences using the NCBI BLAST tool revealed 99-100% sequence homology with exogenous ALV viral envelope protein. Phylogenetic analysis based on partial envelope sequences showed the Malaysian isolate clustered with Taiwanese and Japanese ALV strains, which were closer to ALV subgroup J, ALV subgroup E, and recombinant A/E isolates. Based on these findings, ALV was concluded to be associated with the present outbreak. It was recommended that further studies should be conducted on the molecular epidemiology and pathogenicity of the identified virus isolate.